Efeito de níveis de ferro e radiação ultravioleta no crescimento e produção de microcistina em Microcystis aeruginosa Kützing NPLJ-4 - Lázaro, Georgette Cristina Salvador (2012)
This research aimed to simulate and evaluate the impact of environmental variables (iron and UV-C) on M. aeruginosa (NPLJ-4) growth and MCY production. This strain was cultivated under controlled conditions. The iron assay did not show significant difference of cell density, biovolume and chlorophyll-a between different iron concentrations, while the growth rate, duplication time and toxin concentration showed that difference. More cell divisions (G) were observed with a lower rate at highest iron content cultures, inducing a cell density and biomass increase. The cell divisions were reduced to a lower rate until the iron become scarce (10, 4, 1 e 0.5 μM, respectively). 0.5 μM cultures registered higher growth rate and lower duplication time, cell density and biovolume. Log (6th to 14th day) and stationary (16th to 35th day) phase influenced the high total MCY-LR values of iron cultures. MCY-LR content increased from 10th to 20th day and reduced in 30th day in the 4 and 10 μM iron cultures. 1 μM iron treatment showed higher cell density, biovolume, biggest area peaks and total MCY-LR concentrations in comparison with 0.5, 4 and 10 μM cultures, respectively. Thus, M. aeruginosa growth is not always related to high iron levels and one cell, alone, can be responsible for the production of high toxin content. On the other hand, in the UV-C radiation exposure simulation experiment, complete total MCY-LR remotion was reached in ASM-1 medium with M. aeruginosa bloom, with more than 50% of the toxin degraded at the two initial hours of exposure. The total MCY-LR, cell density, biovolume and chlorophyll-a reduced as the UV-C exposure time increased. Finally, did not occurred MCY-LA and MCY-RR production in the experiments